2015
DOI: 10.1007/s11063-015-9478-6
|View full text |Cite
|
Sign up to set email alerts
|

Computation by Time

Abstract: Over the last years, the amount of research performed in the field of spiking neural networks has been growing steadily. Spiking neurons are modeled to approximate the complex dynamic behavior of biological neurons. They communicate via discrete impulses called spikes with the actual information being encoded in the timing of these spikes. As already pointed out by Maass in his paper on the third generation of neural network models, this renders time a central factor for neural computation. In this paper, we i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…Non-spiking neural networks represent activation as a number to mimic the spike rate of a neuron population whereas spiking neurons represent activation as temporal events, communicating through action potentials called spikes. Importantly, spiking neuron models are able to incorporate time (Walter et al, 2016 ) because biological studies indicate that neurons communicate through frequency of spikes as well as precise spike timing (Bohte, 2004 ). Spiking neuron models have also been shown to use fewer neurons for modeling some computations (Maass, 1997 ).…”
Section: Introductionmentioning
confidence: 99%
“…Non-spiking neural networks represent activation as a number to mimic the spike rate of a neuron population whereas spiking neurons represent activation as temporal events, communicating through action potentials called spikes. Importantly, spiking neuron models are able to incorporate time (Walter et al, 2016 ) because biological studies indicate that neurons communicate through frequency of spikes as well as precise spike timing (Bohte, 2004 ). Spiking neuron models have also been shown to use fewer neurons for modeling some computations (Maass, 1997 ).…”
Section: Introductionmentioning
confidence: 99%
“…Experimental evidence accumulated during the last few years has indicated that many biological neural systems use the timing of single-action potentials (or “spikes”) to encode information (Maass, 1997 ), rather than the traditional rate-based models. In Walter et al ( 2015a ), it is explained that how the exact modeling of time in spiking neural networks serves as an important basis for powerful computation based on neurobiological principles.…”
Section: Primary Motivation and Frameworkmentioning
confidence: 99%
“…The spike trains are used to represent and process the neural information in spiking neurons, which can integrate many aspects of neural information, such as time, space, frequency, and phase, etc. (Whalley, 2013; Walter et al, 2016). As a new brain-inspired computational model of the neural network, SNN has more powerful computing power compared with a traditional neural network model (Maass, 1996).…”
Section: Introductionmentioning
confidence: 99%